2017
DOI: 10.1080/07908318.2017.1304954
|View full text |Cite
|
Sign up to set email alerts
|

Young children capitalising on their entire language repertoire for language learning at school

Abstract: While translanguaging has been well researched in bilingual settings with older pupils and has been found to contribute to cognitive and personal development, there is little research on translanguaging of young multilinguals. In trilingual Luxembourg, at school, children learn Luxembourgish aged 4, German aged 6 and French aged 7, with the majority not speaking Luxembourgish on school entry. The number of languages to be learned may leave teachers little space to capitalise on home languages and encourage tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 27 publications
3
44
0
3
Order By: Relevance
“…While extensive research has been carried out on translanguaging involving two or three (often official) languages, research on translanguaging involving multiple languages, including the home languages, is relatively rare [10,15]. Due to its diverse linguistic landscape, the educational context in Luxembourg is particularly suitable to explore this type of translanguaging.…”
Section: Translanguaging and Translanguaging Pedagogiesmentioning
confidence: 99%
See 1 more Smart Citation
“…While extensive research has been carried out on translanguaging involving two or three (often official) languages, research on translanguaging involving multiple languages, including the home languages, is relatively rare [10,15]. Due to its diverse linguistic landscape, the educational context in Luxembourg is particularly suitable to explore this type of translanguaging.…”
Section: Translanguaging and Translanguaging Pedagogiesmentioning
confidence: 99%
“…Conversely, recent studies [10] show that in some Luxembourgish preschool classes as well as in some Year 1 and Year 2 classes, teachers have begun to encourage the deployment of the students' full linguistic repertoires, including their home languages to some extent. Despite the implementation of a flexible multilingual pedagogy in these classes, Kirsch [10] has found that the children's language practices differ significantly in terms of the languages involved. Whereas kindergarteners are deploying all the features of their repertoires while engaging in translanguaging practices, the primary school children in Years 1 and 2 only rarely use their home languages and flexibly move between Luxembourgish and one of the target languages.…”
Section: Translanguaging In Primary Schools In Luxembourgmentioning
confidence: 99%
“…Teachers have the ability to be language policy makers (Johnson 2013;Menken and García 2010), although contextual constraints greatly limit what they can achieve. In her work with younger learners in Luxembourg, Kirsch (2018) has pointed to the importance of teachers developing a multilingual learning environment to support learning tasks and curriculum that allow students to engage in translanguaging as part of their learning process. In the United States, Allard (2017) illustrated how translanguaging practices performed by teachers and students in the classroom were viewed in relation to other institutional or contextual structures.…”
Section: Conceptual Framework: Translanguaging and Classroom Assessmentmentioning
confidence: 99%
“…Neumann (2015) describes the language situation as one of "linguistic superdiversity", whereby the choice of language depends on the interlocutor, the situation and the private or public domain. "Translanguaging" is an everyday reality (Kirsch, 2017).…”
Section: Early Childhood Education In Multilingual Luxembourgmentioning
confidence: 99%